Review: Rice momilactones, potential allelochemical for weeds suppression - ESTIATI, AMY (Asian Journal of Agriculture, 2019)
Abstract. Estiati A. 2019. Rice momilactones, potential allelochemical for weeds suppression. Asian J Agric 3: 6-15. Weeds become one of the important biological constraint declining the productivity and quality of rice. Among the weeds, barnyardgrass is reported as the most destructive weed species. Synthetic herbicides are preferred method to control weeds. However, the excessive and continuous use of synthetic herbicides can have a negative impact on the environment, health and even the emergence of herbicide-tolerant weeds. Therefore, another alternative to overcome weed problems become the concern of scientists. Rice plants have been proven to be able to suppress the growth of weeds nearby by secreting secondary metabolites called allelochemicals. In this article, the achievements of research on rice allelochemicals at laboratory level will be reported. Among rice allelochemicals, momilactones are potential growth inhibitor. The biosynthetic pathway of momilactones and its coressponding genes have been extensively investigated in rice. OsCPS4, OsKSL4, CYP99A2, CYP99A3 and OsMAS are genes that co-regulated in momilactones biosynthetic pathway and production, and they form a gene cluster which is located on chromosome 4. Reverse genetic approach by inserting genes knock-out of OsCPS4 and OsKSL4 into two rice cultivars from Japonica subspecies showed that insertional mutant lines harboring cps4 or ksl4 exhibited a significant loss in inhibition potential due to the lack of momilactones production.